Peran Mahasiswa Dalam Meningkatkan Kesadaran Kesehatan Remaja - Fatimah Azzahra Sitepuh; Nurainun Ramadani Simanjuntak; Salsabila Azwita Nasution; Usiono U (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to explore the role of college students in increasing health awareness among adolescents, as well as to understand the factors that influence healthy behavior and social awareness. Focusing on students of the State Islamic University of North Sumatra, this study used qualitative methods including interviews and observations to collect data. The results showed that college students have great potential as agents of change in society, especially in terms of health education and social support. College students who have good knowledge about health tend to adopt a healthy lifestyle and participate in programs that care for others. In addition, social support from peers and family has been shown to contribute positively to adolescent mental health. This study recommends the development of health programs that involve college students to increase awareness and healthy behavior among adolescents, and emphasize the importance of nutrition education and mental health. Thus, it is hoped that a generation of healthy and caring adolescents can be realized, contributing to the development of a better society.